2012
DOI: 10.14238/pi52.3.2012.132-7
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin as migraine prophylaxis in adolescents

Abstract: Background Migraine is a cause of recurrent headaches in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…However, a randomized control trial on 48 children with episodic migraine failed to show any difference between a 50% lower dose of 200 mg riboflavin and placebo in reducing the number of headache days, their duration, or the severity of migraine attacks and associated symptoms [ 10 ]. These results are in contrast with the study by Athaillah et al [ 11 ] who performed a randomized controlled trial on 98 adolescents between the ages of 12 and 19. In this study, episodic migraineurs both with and without aura were randomly assigned to receive either placebo or riboflavin 400 mg.…”
Section: Nutraceuticalscontrasting
confidence: 98%
“…However, a randomized control trial on 48 children with episodic migraine failed to show any difference between a 50% lower dose of 200 mg riboflavin and placebo in reducing the number of headache days, their duration, or the severity of migraine attacks and associated symptoms [ 10 ]. These results are in contrast with the study by Athaillah et al [ 11 ] who performed a randomized controlled trial on 98 adolescents between the ages of 12 and 19. In this study, episodic migraineurs both with and without aura were randomly assigned to receive either placebo or riboflavin 400 mg.…”
Section: Nutraceuticalscontrasting
confidence: 98%
“…The first positive report of riboflavin benefit in paediatric or adolescent patients was a Class I AHA/ANN study of 98 adolescent patients (aged 12‐19 years old) with IHS criteria headache. Patients were randomized in a double‐blind controlled format to receive either 400 mg/d of riboflavin or placebo for 3 months.…”
Section: Resultsmentioning
confidence: 99%
“…A critical review of the available clinical evidence for the usefulness of riboflavin in migraine headache brings to light many questions. The majority of single ingredient adult trials have been 3 months 40,43,44,52 in duration with one exception. 42 In addition to a critical evaluation of clinical trial data, questions arise from the available pharmacokinetic and pharmacogenomic data.…”
Section: What Is New and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous systematic reviews that evaluated the role of riboflavin in the prevention of migraine assessed the same studies (three RCTs and one retrospective study) [ 20 , 21 ]. Among these studies, two—one RCT and one retrospective study—reported that riboflavin was effective [ 22 , 23 ], while the other two reported ineffectiveness [ 24 , 25 ]. The latter two studies concluded that there was a lack of evidence to support the use of riboflavin for pediatric migraine.…”
Section: Resultsmentioning
confidence: 99%